(Invited) High Performance Nano-Ceria Electrodes for Solid Oxide Cells. (26th April 2016) - Graves, Christopher; Martinez, Lev; Sudireddy, Bhaskar Reddy
Abstract : In solid oxide electrochemical cells, the conventional Ni-based fuel-electrodes provide high electrocatalytic activity but they are often a major source of long-term performance degradation due to carbon deposition, poisoning of reaction sites, Ni mobility, etc. Doped-ceria is a promising mixed ionic-electronic conducting oxide that could solve these issues if it can be integrated into an appropriate electrode structure. Two new approaches to obtain high-performance nanostructured doped-ceria electrodes are highlighted. The first is an infiltration-based architecture with Ce0.8 Pr0.2 O2-δ forming the active surfaces on a porous backbone with embedded electronic current collector material, yielding one of the highest performances reported for an electrode that operates either on fuel or oxidant. The second is a nano-Ce0.9 Gd0.1 O2-δ thin film prepared by spin-coating, which provides an unprecedented electrode polarization resistance of 0.01 Ω cm 2 at 650 °C in H2 /H2 O. These results demonstrate that nano-ceria has the ability to achieve higher performance than Ni-based electrodes and show that the main challenge is obtaining sufficient electronic current collection without adding too much inactive material.